Stabilization of the Transcription Factor Foxp3 by the Deubiquitinase USP7 Increases Treg-Cell-Suppressive Capacity - van Loosdregt, Jorg (2013)
Stable Foxp3 expression is required for the development of functional regulatory T (Treg) cells. Here, we demonstrate that the expression of the transcription factor Foxp3 can be regulated through the polyubiquitination of multiple lysine residues, resulting in proteasome-mediated degradation. Expression of the deubiquitinase (DUB) USP7 was found to be upregulated and active in Treg cells, being associated with Foxp3 in the nucleus. Ectopic expression of USP7 decreased Foxp3 polyubiquitination and increased Foxp3 expression. Conversely, either treatment with DUB inhibitor or USP7 knockdown decreased endogenous Foxp3 protein expression and decreased Treg-cell-mediated suppression in vitro. Furthermore, in a murine adoptive-transfer-induced colitis model, either inhibition of DUB activity or USP7 knockdown in Treg cells abrogated their ability to resolve inflammation in vivo. Our data reveal a molecular mechanism in which rapid temporal control of Foxp3 expression in Treg cells can be regulated by USP7, thereby modulating Treg cell numbers and function.